2013
DOI: 10.1890/es12-00322.1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of terrestrial subsidies for estuarine food webs in contrasting East African catchments

Abstract: Abstract. Little is known on the degree to which terrestrial organic matter delivered to tropical estuaries contributes to estuarine consumers. Here, stable isotope analysis is used to constrain this contribution for contrasting east African estuaries whose catchments differ in relative C3/C4 vegetation cover. As these two types of vegetation differ strongly in d 13 C, we anticipated that terrestrial subsidies would be reflected in a gradient in estuarine consumer d13 C values, following the relative importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 93 publications
1
67
0
Order By: Relevance
“…The environmental characteristics of each system are described in Table and more extensively in Abrantes et al . ().…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The environmental characteristics of each system are described in Table and more extensively in Abrantes et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…Bayesian mixing models confirmed that C4 material from the catchment was the most important source for the highly turbid, C4‐dominated estuaries, whereas for the less turbid C3‐dominated estuaries terrestrial subsidies were not as important and consumers relied on a combination of terrestrial and aquatic sources (Abrantes et al . ). In the present study, the effect of environmental conditions such as dominant catchment vegetation and turbidity on estuarine food webs is further investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Terrestrial forest plants typically have isotope values similar to mangroves (Abrantes et al 2013), so any contribution of terrestrial matter to the food webs, for example via riverine input (Wissel and Fry 2005), cannot be separated from that of mangroves. This possibility could be important for management of land-uses in coastal catchments and could be pursued in future with additional biomarkers capable of separating mangroves from terrestrial plants (e.g., Dittmar et al 2006).…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…Supporting this view are a number of recent stable isotope studies suggesting that allochthonous DOC can provide a significant subsidy to pelagic zooplankton and fish in lakes (Cole et al ; Karlsson et al ; Tanentzap et al ) and estuarine and coastal systems (Hoffman et al ; Abrantes and Sheaves ; Hitchcock et al ; Von Biela et al ). Significantly, many of these studies have identified that the magnitude of allochthonous subsidy varies with environmental conditions, especially hydrological events (Abrantes et al ). For example, Hoffman et al () showed in the York River estuary, U.S.A., that the contribution of allochthonous carbon to cladocera and copepod diets increased during wet years, while Atwood et al () showed that terrestrial carbon made a significant contribution to zooplankton biomass following storms in the tropical estuary of Hilo Bay, Hawaii.…”
mentioning
confidence: 99%